Documentation of NEMO - Norges Bank's Core Model for Monetary Policy Analysis and Forecasting - Karsten R. Gerdrup; Erling Motzfeldt Kravik; Kenneth Sæterhagen Paulsen; Ørjan Robstad (Norges Bank, 2017)
This paper explains the basic mechanisms of Norges Bank's core model for monetary policy analysis and forecasting (NEMO). NEMO has recently been extended with an oil sector to incorporate important channels of shocks to the Norwegian economy. We show how the effects of a change in the oil price depends on whether the price change is due to demand or supply factors in the international economy. Other extensions of the model include a more detailed modeling of the foreign sector. The paper also uses NEMO to highlight important driving forces of the Norwegian economy after the fall in the oil price. We demonstrate that the model has a reasonable empirical fit compared to VAR models.
hdl:11250/2506373
Keywords: E12; E52; G01; 330; DSGE; monetary policy